Practical pricing and the restaurant industry - Choi, Sunmee (Henry Stewart Talks, 2009)
What is revenue management?, Time perishable inventory, Time variable demand, Revenue management strategies, Menu pricing approaches, Are we charging the optimal price?, Menu re-engineering, What should be the menu of the day?, Pricing to stimulate demand, Profit impact of discounting, Selling strategy, What do restaurants sell?